2021
DOI: 10.3389/fendo.2021.797049
|View full text |Cite
|
Sign up to set email alerts
|

Does Diabetes Mellitus Increase the Short- and Long-Term Mortality in Patients With Critical Acute Myocardial Infarction? Results From American MIMIC-III and Chinese CIN Cohorts

Abstract: BackgroundThe harmful effect of diabetes mellitus (DM) on mortality in patients with acute myocardial infarction (AMI) remains controversial. Furthermore, few studies focused on critical AMI patients. We aimed to address whether DM increases short- and long-term mortality in this specific population.MethodsWe analyzed AMI patients admitted into coronary care unit (CCU) with follow-up of ≥1 year from two cohorts (MIMIC-III, Medical Information Mart for Intensive Care III; CIN, Cardiorenal ImprovemeNt Registry) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…First, we are limited to variables measured and end points published in each study, as with many meta-analyses. Also, many recently published studies related to the topic did not provide sex-specific post-AMI all-cause mortality in both patients with and without diabetes, thus they can’t be included in the review ( 54 56 ). Although we followed the PRISMA guidelines and used an extensive search strategy to identify existing literature in multiple databases, the majority of the included studies were observational cohort studies with greater potential for bias and between-study heterogeneity than randomized controlled trials ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…First, we are limited to variables measured and end points published in each study, as with many meta-analyses. Also, many recently published studies related to the topic did not provide sex-specific post-AMI all-cause mortality in both patients with and without diabetes, thus they can’t be included in the review ( 54 56 ). Although we followed the PRISMA guidelines and used an extensive search strategy to identify existing literature in multiple databases, the majority of the included studies were observational cohort studies with greater potential for bias and between-study heterogeneity than randomized controlled trials ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…Prevalence of DM in AMI patients varied from 20-30% (Arnold, 2014), but it keeps increasing (Gandhi, 2006). Based on a study in 2021 between two cohorts from American and Chinese, the result showed DM is often find in critical AMI patients (almost half and one-third) (Chen, 2021). According to a study in Qatar, as much as 54% prevalence of DM was shown in critical AMI patients (El-Menyar, 2009).…”
Section: Type 2 Diabetes Mellitus and Acute Myocardiac Infarctionmentioning
confidence: 99%
“…DM used as a good predictor for prognostic in AMI patients. In patients with AMI, DM contribute to 2 until 9 times higher risk of death (Chen, 2021). During a study in Italy, the death of DM patients with STEMI was also trigger by the predominant factors of the patients who have cardiorenal dysfunction (Marenzi, 2019).…”
Section: Type 2 Diabetes Mellitus and Acute Myocardiac Infarctionmentioning
confidence: 99%
“…All analysis processes were finished with R software (version 4.2.2). In cleaning clinical data, the R packages nhanesR (version 0.9.4.1) were served for NHANES, and pgAdmin PostgreSQL (version 14.1) [20][21][22] was applied in MIMIC.…”
Section: Statistical Analysesmentioning
confidence: 99%